Immigration Biometric Data Exchange Among Asean Member States: Opportunities and Challenges in Legislations - Mohammad Thoriq Bahri (Badan Strategi Kebijakan Hukum, 2022)
Biometric data can be described as data containing human physical characteristics. They can be in the form of fingerprint data, retina scans, and voice recognition. The application of biometrics for immigration purposes reduce the number of terrorism case and illegal migrants in the European Union (EU) territory and the United States. In 2013, biometric data exchange in ASEAN was made possible with the Bali Process Protocol. By a qualitative research methodology, using the CIPP (Context, Input, Process, and Product) analysis, this research attempts to find the legal obstacles as the main barriers in implementing biometric data exchange in the ASEAN region. This study finds that not all ASEAN countries have laws on personal data protection, which affect the Standard Operating Procedures (SOP) related to how the biometric data will be retrieved, processed, and managed, as well as the actions required if there is a violation of the law related to the SOP. This study suggests that ASEAN can accommodate the EU's framework, by using the General Data Protection Regulation (GDPR) as a single standard in the application of Data Protection regulations for the biometric data exchange system in ASEAN.